Health Impact Assessment in protected areas: a proposal for urban contexts in Brazil - Ana Schramm; Sandra de Souza Hacon; Andre Reynaldo Santos Périssé (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: The use of Health Impact Assessment (HIA) in the establishment of an urban protected area can enhance the positive impacts and mitigate the negative impacts resulting from its implementation. Brazil hosts some of the most important biodiversity hotspots in the world and the HIA may benefit biodiversity and human health. These areas are commonly created without any preceding survey to assess their impacts on health. Protected areas located in urban zones are essential to maintain environmental balance and quality of life in cities. It promotes positive impacts on health, providing ecosystem services and salutogenic benefits. However, they can generate negative impacts such as the violation of human rights, property speculation, spread of vectorial diseases, and psychosocial stress. Based on the identification of the potential impacts of urban protected areas on health and best practices, this qualitative and exploratory study justifies the use of HIA in urban protected areas, especially in the Brazil, and indicates the main elements for the construction of a methodological approach to contribute to the Sustainable Development Goals and one of its alternatives, the Buen Vivir approach.